Approximation of the classes $C_{β}^{ψ} H_{ω}$ by generalized de la Valiée-Poussin sums - Novikov, O. A.; Rukasov, V. I. (Ukrains’kyi Matematychnyi Zhurnal, 1997)
On the classes of periodic functions $C_{β}^{ψ} H_{ω}$, we study approximating properties of trigonometric polynomials generated by methods for summation of Fourier series.